A Study on the Adaptation Systems for Rural Water Supply and Sanitation Sector to Respond to Climate Impact in Svay Rieng Province, Cambodia - Keo Hak; Serey Mardy; Sang-Min Han (International Journal of Sustainable Applied Sciences, 2023)
Lack of improved water, sanitation, and hygiene (WASH) is a high risk for people who are living in urban and rural areas in Svay Rieng province. This study has three objectives: (a) to assess the current impact of climate change on rural WASH; (b) to examine the adaptation systems of rural WASH as they respond to climate change; and (c) to determine the elements of appropriate mechanisms and supporting systems for the sustainability of rural WASH's climate change adaptation. As a methodology, this research surveyed 136 samples from 8 districts in Svay Rieng province. The results found that knowledge and awareness of people on climate change were at 92.65%. The main factors that cause climate change are burning fossil fuels like oils, gasoline, and coal. The sensitive sectors impacted by climate change are water and sanitation. There are two kinds of elements: appropriate mechanisms and supporting systems for the sustainability of rural water supply. To improve future rural WASH in local communities and adaptation to climate change, people should focus on using high-tech infrastructure for water supply stations such as safe water pipe systems, water treatment stations, pump wells, and ponds that are resilient and adapt to climate impact.